Soil nitrogen transformation and functional microbial abundance in an agricultural soil amended with biochar - Junnan Ding (Revista Brasileira de Ciência do Solo, 2023)
ABSTRACT Biochar soil amendments are attracting attention as one strategy to improve soil microbially ecological environment and regulate the soil nitrogen cycle. This study aimed to evaluate the effects of biochar application on agricultural soil improvement, nitrogen (N) mineralization and nitrification. The experiment was carried out on a typical farmland containing black soil and saline-alkaline soil in Northeast China. Four treatments were undertaken, including the control-treated black soil farmland (CS), the biochar-treated black soil farmland (BCS), the control-treated saline-alkali soil farmland (SAS), and the biochar-treated saline-alkaline soil farmland (BSAS). Basic physical and chemical properties, enzyme activity, and the contents of ammonium-nitrogen (NH4+-N) and nitrate-nitrogen (NO3--N) in the soil were subsequently determined. The co-occurrence networks of bacterial communities of the biochar and control treatment groups were constructed based on high-throughput sequencing data of the 16S rRNA genes. The results showed that the BCS and BSAS treatments significantly increased the contents of soil organic matter, total nitrogen, total phosphorus, and available phosphorus. The application of biochar significantly increased the NH4+-N contents in the black soil and saline-alkaline soil by 81.78 and 80.08 %, respectively, while significantly reducing the soil NH4+-N/NO3--N content, which promoted the transformation of NH4+-N into NO3--N. Subsequently, the released NH4+-N was transformed into NO3--N through nitrification. After the biochar application, the NO3--N contents in the black and saline-alkaline soils could be fixed. The biochar application significantly increased the abundance of gdh, AOA-amoA, AOB-amoA, nirK, nirS, nosZ, and nifH genes, with no significant difference in the abundance of napA genes being found among different treatments. Microbes playing a key role in the co-occurrence network were Proteobateria, Acidobacteria, Bacteroidetes, Actinobacteria, and Chloroflexi. As compared with the CS and SAS treatments, under the BCS+BSAS treatment, the connectors, module hubs, connectedness, and clustering coefficient showed larger parameters, and the networks were more complex. The application of biochar gradually increased the nodes, edges, and average degree of the bacterial co-occurrence network, thus indicating that the interaction between microbial groups in the black and saline-alkaline soils post biochar application may be important in the biogeochemical cycle process in farmland soil.